Bonjour,
1)[tex]E = \left(3x-2\right)-\left(3x-2\right)\left(x-3\right)\\ E = \left(9x^2-12x+4\right)-\left(3x^2-9x-2x+6\right)\\ E =9x^2-12x+4-3x^2+11x-6\\ E = 6x^2-x-2\\[/tex]
2)
[tex]E = \left((3x-2\right)^2-\left(3x-2\right)\left(x-3\right)\\ E = \left(3x-2\right)\left[\left(3x-2\right)-\left(x-3\right)\right]\\ E = \left(3x-2\right)\left(3x-2-x+3\right)\\ E = \left(3x-2\right)\left(2x+1\right)[/tex]
3)[tex]E = 6x^2-x-2\\ E = 6\times 0^2-0-2\\ E = -2[/tex]
4)On a :
[tex]\left(3x-2\right)\left(2x+1\right) = 0[/tex]
Si un produit est nul, alors l'un de ses facteurs est nul.
Donc :
[tex]3x-2 = 0\\ 3x = 2\\ x = \frac 23[/tex]
Ou :
[tex]2x+1 = 0\\ 2x = -1\\ x = -\frac 12[/tex]